Repeated sprint variations according to circadian rhythm at different menstrual cycle phases - Kulaksiz, T. N.; Kosar, S. N.; Hazir, T.; Kin-Isler, A. (International Journal of Sports Medicine, 2025)
This study assessed the repeated sprint performance in relation to circadian rhythm during different menstrual cycle phases (MCP). Twelve volunteer eumenorrheic women team sport athletes performed 5×6-s cycling sprints in morning (9 am to 10 am) and evening (6 pm to 7 pm) sessions during the mid-follicular (FP, 6th-10th d) and luteal phases (LP, 19th-24th d). Body weight, oral body temperature, resting heart rate and lactate levels together with estradiol, progesterone and cortisol levels were determined before tests. Relative peak and mean power and performance decrements were determined as performance variables and maximum heart rate, lactate and ratings of perceived exertion were determined as physiological variables. Evening body temperatures were significantly higher. Cortisol levels were higher in the morning and in the FP. Resting lactate levels did not vary with MCP or time of day, but a significant MCP x time of day interaction was observed. Body weight showed no change according to time of day and MCP. There was no significant effect of MCP and time of day on performance and physiological variables, in contrast, maximum lactate values were notably higher in the evening. In conclusion, MCP and time of day need not be considered during repeated sprint exercises of eumenorrheic women athletes.